2022
DOI: 10.3390/w14233918
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination with Micro- and Nanoplastics Changes the Phototaxis of Euryhaline Zooplankton to Paired Photostimulation

Abstract: Our earlier studies showed that paired photostimulation allows the detection of pollutants in an aqueous medium according to the behavioral responses of freshwater Crustacea. The first stimulus initiated and stabilized the behavioral response. The increase in response to the second stimulus made it possible to assess the responsiveness of the zooplankton community. This paper studies the validity of this method for the detection of micro- and nanoplastic contamination of saltwater reservoirs according to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Previously, in laboratory conditions, we showed that the inhibition of phototaxis to the paired photostimulation is a fairly sensitive and stable indicator of such pollutants as micro-and nanoplastics, oil, and standard potassium dichromate toxicant [28,29]. This study additionally registered the characteristics of plankton communities, such as the age variability according to the Shannon index and the presence of cyclic variability in behavioral phototropic response based on the spectral analysis of the pPhR time series.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previously, in laboratory conditions, we showed that the inhibition of phototaxis to the paired photostimulation is a fairly sensitive and stable indicator of such pollutants as micro-and nanoplastics, oil, and standard potassium dichromate toxicant [28,29]. This study additionally registered the characteristics of plankton communities, such as the age variability according to the Shannon index and the presence of cyclic variability in behavioral phototropic response based on the spectral analysis of the pPhR time series.…”
Section: Discussionmentioning
confidence: 90%
“…Under laboratory conditions, we found [28] that the greatest response rate was observed with the use of the paired photostimulation according to the scheme of "the first stage of photostimulation 5 min, 25% of maximum illuminance + second stage 5 min, 75%" (illuminance as a percentage of maximum illuminance provided by the laser, 1150 lx, and 3450 lx, respectively).…”
Section: Choice Of Paired Photostimulation Illuminance Ratiomentioning
confidence: 94%
See 1 more Smart Citation
“…In a number of publications, we used the phototropic response of plankton with its photostimulation with attractor radiation to solve the biondication tasks. This requires placing a second source of laser radiation into the DHC, and in the latest modificationsa third source is added to excite the laser induced fluorescence to study phytoplankton [17][18][19].…”
Section: Equipment and Dhc Technology For Bioindicationmentioning
confidence: 99%
“…The response of zooplankton to photostimulation changes against the background of the changed physiological state of hydrobionts when pollutants act [42,43]. Although, to date, the mechanism of this impact on zooplankton remains poorly understood, laboratory and field studies showed that photostimulation provides early detection of pollutants in the water medium according to behavioral responses [44].…”
Section: Introductionmentioning
confidence: 99%